Analysis of The Occurrence of repeated BPK Audit Findings in The Financial Statements of a Government Institution - Fadhila Nurfida Hanif; Yos Sunitiyoso (Journal of International Conference Proceedings (JICP), 2021)
One tangible manifestation of the implementation of transparency and accountability of government institutions is through the preparation of relevant and reliable government financial reports. To ensure the quality of Government Financial Reports, the State Audit Board (BPK/Badan Pemeriksa Keuangan) audits related to state financial accountability are carried out in order to provide an opinion on the fairness of the information presented in the government's financial statements. Based on the results of BPK audits on government institution, there are still repeated findings, namely findings with the same problems and repeated from year to year. This study aims to determine the factors that cause repeated findings in BPK audit results and propose appropriate strategies to prevent the occurrence of repeated findings. The research technique used is qualitative, with data collection through literature study, data observation of BPK audit results and interviews. Interviews will be conducted with internal parties such as financial managers, asset managers, commitment makers, and internal auditors. In addition, interviews will also be conducted with external parties, namely the BPK auditors. The results showed that the causes of repeated findings were due to man, budget, organization, technology, regulatation factors and internal control factors.